A new method for determination of fluoride ion in commodity tea by ion-exclusion chromatography. Issue 1 (1st January 2018) - Zhou, Lili; Li, Huaiping; Ye, Shanrong; Tan, Heping
ABSTRACT: Due to the effect of interfering ion, the content of fluoride ion in tea brew, detected by ion-exchange chromatography, was markedly higher than ion-selective electrode. Ion-exclusion chromatography, a new method for the determination of fluoride ion in tea brew, was proposed and evaluated in this study. Two Metrosep organic acid columns in series resulted in better separation of fluoride ion than single column. The most suitable organic modifier for eluent and its percentage were checked, the optimal conditions of the mobile phase was 0.33 mM sulfuric acid solution containing 10.5% (v/v) acetone, at a flow rate of 0.5 mL/min. Satisfactory sensitivity and wide linearity range were obtained. The applicability of the method was demonstrated by the analysis of various tea samples in China, the accuracy of the results was proved by recovery tests, and the concordance with the values was obtained by ion-selective electrode.